ACUTE AND SUBACUTE TOXICITY OF SIDDHA FORMULATION DHATHU BHUSTI CHOORANAM - Thangadurai, K. (International Journal of Ayurveda and Pharma Research, 2017)
Dhathu busti chooranam (DBC) is a polyherbal formulation indicated in Siddha literature for the treatment of male infertility. The aim of this research was to evaluate the acute and sub-acute oral toxicity of the drug DBC. The acute toxicity test was conducted using albino rats of either sex. Water extract of DBC was administrated in a single dose of 2000 mg/kg via oral gavage and the animals were observed for any behavioral changes or mortality. In the sub-acute toxicity study, male albino rats received two doses of DBC (200, 400mg/kg) for 28 days via oral gavage and the rats were observed for toxicity symptoms. Following the 28-day treatment, the rats were sacrificed for hematological, biochemical and histopathology studies. In the acute toxicity study, DBC was found to be non-toxic at a dose of 2000 mg/kg b.w with no signs of mortality. In the sub-acute toxicity study, there was no significant variations in body weight, hematological and biochemical parameters found in the experimental groups at the dose of 200 and 400 mg/kg. The tested dose in experimental rats is significantly higher than the human therapeutic dosage. The acute and subacute toxicity study results show that DBC may be a safe drug without causing any serious side effects.